2016
DOI: 10.1111/trf.13511
|View full text |Cite
|
Sign up to set email alerts
|

Storage of platelets at 4°C in platelet additive solutions prevents aggregate formation and preserves platelet functional responses

Abstract: Storage of AP at 4°C leads to low level GPIIb-IIIa activation and results in aggregate formation over time. Separating the PLTs from the plasma component and storing them in PAS at 4°C resolves aggregate formation and preserves the metabolic and functional responses of these stored PLTs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
202
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(230 citation statements)
references
References 36 publications
22
202
6
Order By: Relevance
“…Although PLTs can be cold‐stored in plasma, an increased risk of PLT clumping during storage due to activation of the glycoprotein (GP) IIb/IIIa receptor and fibrinogen binding can result in a high discard rate . Recent work from our group has shown that cold storage of PLTs in a PLT additive solution (PAS) can minimize cold PLT clumping by dilution of plasma fibrinogen while preserving PLT function for at least 15 days …”
mentioning
confidence: 99%
“…Although PLTs can be cold‐stored in plasma, an increased risk of PLT clumping during storage due to activation of the glycoprotein (GP) IIb/IIIa receptor and fibrinogen binding can result in a high discard rate . Recent work from our group has shown that cold storage of PLTs in a PLT additive solution (PAS) can minimize cold PLT clumping by dilution of plasma fibrinogen while preserving PLT function for at least 15 days …”
mentioning
confidence: 99%
“…Similarly, PAS could play a role in optimizing conditions for cold-stored platelets [16]. This study showed that at 4 ° C the GpIIb/IIIa fibrinogen receptor is activated by the cold and that the use of PAS resulted in less aggregate formation due to dilution of fibrinogen.…”
Section: Pas To Mitigate Lesions Caused By Pathogen Inactivation or Cmentioning
confidence: 91%
“…More recent data showed that alternate storage, such as in platelet additive solution, can lengthen the shelf-life. 23,24 Also the platelets are more hemostatically active, which could be of use in bleeding patients. Although cold-stored platelets are cleared more rapidly, these platelet products may be more suitable for actively bleeding patients, particularly trauma patients.…”
Section: Future Productsmentioning
confidence: 99%